Associations of blood pressure categories defined by 2017 ACC/AHA guidelines with mortality in China: Pooled results from three prospective cohorts. (29th August 2020) - Liu, Na; Yang, Jae Jeong; Meng, Ruiwei; Pan, Xiong-Fei; Zhang, Xiaomin; He, Meian; Li, Honglan; Gao, Yu-Tang; Xiang, Yong-Bing; Shu, Xiao-Ou; Zheng, Wei; Wu, Tangchun; et al.
Abstract: Background: The recent American College of Cardiology/American Heart Association guidelines for high blood pressure lowered the hypertension criteria from systolic/diastolic blood pressure (SBP/DBP) of 140/90 mmHg or greater to 130/80 mmHg or greater, while the potential impact of the change on Chinese adults remains unclear. Design: A pooled prospective cohort analysis. Methods: Included were 154, 407 Chinese adults from three prospective cohorts, which measured blood pressure at baseline and follow-up visits, and tracked death events by linkages to medical insurance system or vital statistics registries. Cox regression models were used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs). Results: During a total follow-up of 1, 718, 089 person-years, 14, 692 deaths were documented including 5086 cardiovascular deaths (1277 ischaemic heart disease and 2509 cerebrovascular disease deaths). Compared to normal blood pressure (SBP/DBP < 120/80 mmHg), newly defined stage 1 hypertension (SBP/DBP 130–139/80–89 mmHg) was associated with increased cardiovascular mortality (HR 1.40, 95% CI 1.16–1.69; HR 1.36, 95% CI 1.12–1.65 for ischaemic heart disease mortality; HR 1.53, 95% CI 1.18–2.00 for cerebrovascular mortality), but not with all-cause mortality (HR 1.04, 95% CI 0.89–1.21). Stage 2 hypertension (SBP/DBP ≥ 140/90 mmHg) showed significant associations with cardiovascular disease and all-cause mortality, while elevated blood pressure (SBP 120–129 mmHg and DBP < 80 mmHg) showed null associations. The associations were stronger in adults younger than 65 years and adults without pre-existing cardiovascular disease compared with their counterparts ( P for heterogeneity < 0.05). Conclusions: The newly defined stage 1 hypertension is associated with an increased risk of cardiovascular disease mortality in the Chinese population, particularly among younger adults and those without a history of cardiovascular disease.